O Museu de História Natural de Mato Grosso Casa Dom Aquino : uma proposta de ensino da geografia por meio da educação patrimonial - Silva, Marinete Guimarães da (2023)
Heritage education emerged in Brazil in the 1980s, from the discussions related to the preservation of cultural heritage. In the context of school geography, research in this area is recent and its teaching is essential so that individuals can value and appropriate the local culture, strengthening memory, citizenship, and regional identity. The city of Cuiabá has great potential for research and heritage education, considering the existence of nineteen museums, historical sites such as the historical city center nationally listed, urban, and rural archaeological sites, natural sites, monuments, and buildings dating from the eighteenth century and that testify to the history of the city with more than three centuries of existence. The museum spaces mentioned above guard various types of collections, and for this research the Museum of Natural History of Mato Grosso Casa Dom Aquino was chosen, because this institution safeguards archaeological remains and communicates to the public the prehistory of the state and the original peoples. The choice for this museum was also since it is open for visitation, from 2021 to 2023, in time of the COVID-19 pandemic. In these terms, we sought to understand how the proposal of heritage education contributes to the construction of geographical knowledge and is an instrument of appreciation of the heritage of Cuiabá- MT. This is a qualitative and exploratory research, in which surveys and bibliographic analyses were carried out on heritage education, heritage, citizenship and the teaching of geography, as well as on-site visits for data collection. As a result, this research addressed the patrimonial assets in Mato Grosso; contextualized the Natural History Museum of Mato Grosso Casa Dom Aquino, the thematic rooms and the educational and inclusive actions that take place during the year 2021; and suggested a script of pedagogical activities to geography teachers outside the school environment, to be carried out with elementary school students. In addition to these professionals, the proposal suggests teaching geography through the study of a heritage asset and can be carried out with individuals of all ages, who attend schools or not, since geography is everywhere and can happen in all spaces. It is noteworthy that the museum object of this research is a unique place, endowed with singularities, being a reference in archaeology, paleontology, and indigenous peoples in the state of Mato Grosso. Created on December 7, 2006, the museum began its activities in the house/headquarters of the Bela Vista farm, built in colonial style in the nineteenth century, located on the banks of the Cuiabá River. Therefore, it is a cultural equipment of geographical, archaeological, and historical relevance.